2019
DOI: 10.1155/2019/2709486
|View full text |Cite
|
Sign up to set email alerts
|

Applying Pulse Spectrum Analysis to Facilitate the Diagnosis of Coronary Artery Disease

Abstract: Not all patients with angina pectoris have coronary artery stenosis. To facilitate the diagnosis of coronary artery disease (CAD), we sought to identify predictive factors of pulse spectrum analysis, which was developed by Wang and is one technique of modern pulse diagnosis. The patients suffered from chest pain and received cardiac catheterization to confirm the CAD diagnosis and Gensini score were recruited. Their pulse waves of radial artery were recorded. Then, by performing a fast Fourier transform, 10 am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…To measure radial pulse signals, a series of acquisition devices have been developed and applied in pulse acquisition ( Luo et al, 2012a ; Qiao et al, 2018 ; Tsai et al, 2018 ; Fu et al, 2019 ; Huang et al, 2019 ). These devices employ sensors with one sensing element to capture radial pulse signals.…”
Section: Introductionmentioning
confidence: 99%
“…To measure radial pulse signals, a series of acquisition devices have been developed and applied in pulse acquisition ( Luo et al, 2012a ; Qiao et al, 2018 ; Tsai et al, 2018 ; Fu et al, 2019 ; Huang et al, 2019 ). These devices employ sensors with one sensing element to capture radial pulse signals.…”
Section: Introductionmentioning
confidence: 99%
“…Namun, kepatuhan minum obat sangat didukung oleh pengetahuan yang dimiliki pasien. Kepatuhan minum obat bagi pasien PJK akan dapat dilaksanakan secara baik apabila pasien mengetahui manfaat dari pengobatan yang dianjurkan (2,45,(49)(50)(51)(52).…”
Section: Hubungan Kepatuhan Minum Obat Dengan Kejadian Serangan Berul...unclassified
“…Professors Tsai et al indicated that the harmonic characteristics of the radial artery in the wrist at different positions and different parameters were not identical, and recommended that any measurement location in future studies on the HA of pressure pulse diagnosis needs a more finely adjusted analysis [10]. More importantly, there have been further studies about the HA of radial arterial waveform (e.g., a kind of peripheral pressure pulse) addressing hypertension [11] and monitoring applied to coronary artery disease [12], type 2 diabetes mellitus [13][14][15][16], and the preservation of health [17]. On the other hand, a noninvasive wearable MEMS pressure sensor array was proposed in [18] for monitoring the arterial pulse waveform and heart rate, and the detection of atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%